Freedom of teaching, terrorism and state restrictions: culture of suspected or legitimate defense of the state? - Figueroa Gutarra, Edwin (2018)
Based on an analysis between the notions of democracy and the constitutional state, this study addresses the complex relationships between the fundamental right to freedom of education and terrorism. It is an axis of all public policy to combat terrorism within the framework of the rule of law and in that purpose, the State implements state restrictions on non-readmission for teachers sentenced for terrorism. However, it is necessary to elucidate these questions as to whether they are expressions of a culture of suspicion, or whether in their case they are measures for a legitimate defense of the same State.